Altered Large-Scale Brain Functional Connectivity in Ocular Hypertension - Giorgio, Antonio; Zhang, Jian; Costantino, Francesco; De Stefano, Nicola; Frezzotti, Paolo (Frontiers in Neuroscience, 2020)
We hypothesized that assessment of brain connectivity may shed light on the underpinnings of ocular hypertension (OHT), characterized by raised intraocular pressure (IOP) and no typical glaucomatous findings. OHT carries a risk for future glaucoma development, thus representing a model of presymptomatic condition. In previous studies on glaucoma, we showed altered brain connectivity since early stage and in case of normal IOP. In this pilot study, we used a multimodal MRI approach by modeling voxelwise measures of grey matter volume, anatomical connectivity along white matter tracts and large-scale functional connectivity in OHT subjects (n=18, age: 58.3±9.8 years) and demographically matched normal controls (n=29). While OHT brain had no structural alterations, nonetheless it showed significantly decreased functional connectivity in key cognitive networks (default mode network, frontoparietal working memory network, ventral attention network and salience network) and altered long-range functional connectivity, which was decreased between default mode and salience networks and increased between primary and secondary visual networks. Overall, such findings seem to delineate a complex neuroplasticity in the OHT brain, where decreased functional connectivity in nonvisual networks may reflect a type of temporarily downregulated functional reserve while increased functional connectivity between visual networks may be viewed as a very early attempt of adaptive functional reorganization of the visual system.